Occurrence of Twin Seedlings in Humboldtia Vahliana Wight and Syzygium Mundagom (Bourd.) Chithra-Two Endemic Trees of Southern Western Ghats - Jose, P. A.; Mohanan, N.; Hussain, A. (Indian Forester, 2009)
No abstract